Perebutan Peran dan Hubungan Gender dalam Sistem Matriarkal Masyarakat Minangkabau - Ahmad Hakam (Laboratorium Sosiologi Universitas Nahdlatul Ulama Indonesia Jakarta, 2021)
This study aims to explore the gender roles and relations in the Minangkabau society and how the situation is changing due to some interactions with other influential factors, mainly Islamic teaching and nation-state projection. This article argues that although the Minangkabau matriarchal traditions are influenced by particularly the two driving forces, there have been both continuity and change which prove that the gender roles and relations are a highly contested discourse. This study used library research, and mini- ethnographical approach which involved several field observations and interviews through casual conversation with Minangkabau people. The results show that gender and the conception of women and men are highly contested, especially in the region where more than one influences are competing. Although there is a number of powerful discourse disparities, especially the Islamist movement and the state, the creation and instillation of new definitions and identities of the Minangkabau is reworked within their ideologies of gender and rank, kinship and matriliny.